The Role of Preemptive Infiltration Anesthesia in the Management of Postoperative Pain Following Septoplasty - Yener, Haydar Murat; Akiner, Umur; Sari, Elif; Erdur, Zülküf Burak; Tevetoğlu, Firat; Gözen, Emine Deniz (International Archives of Otorhinolaryngology, 2022)
Introduction Septoplasty is one of the most common surgical procedures in rhinology practice. Two major problems encountered after septoplasty are pain and bleeding. Preoperative administration of analgesics before the surgical stimulus, which is the main concept of preemptive analgesia, decreases postoperative pain.Objective The present study was designed to investigate whether preincisional lidocaine infiltration to the subperichondrial area during septoplasty surgery reduced or not postoperative pain and analgesic use.Methods The present prospective, randomized, placebo controlled, double-blind trial was conducted on 64 consecutive patients with nasal septum deviation. Patients were randomly divided into 2 groups; the study group received 2% 20 mg lidocaine/cc (n = 31), and the control group received 6 cc 0.9% NaCl (n = 33). A standard questionnaire was given to each patient to mark his or her pain score between 0 and 10 at the 1st, 3rd, 6th, 12th, and 24th hours.Results The mean and the range of visual analogue scale (VAS) scores of the patients in the study group at the 1st, 3rd, 12th, and 24th hours were 4.03 ± 3.08 (0–10); 3.42 ± 2.39 (0–8); 2.97 ± 2.22 (0–8); 2.87 ± 2.61 (0–9); and 1.94 ± 2.06 (0–9) respectively. The mean and the range of VAS scores of the patients in the control group at the 1st, 3rd, 12th, and 24th hours were 4.12 ± 2.7 (0–10); 3.45 ± 2.4 (0–10); 2.94 ± 2.7 (0–10); 2.79 ± 2.34 (0–10); and 1.5 ± 1.8 (0–6), respectively. The statistical analysis revealed no significant difference among the groups.Conclusion The preemptive local anesthetic administration to the incision area and under the mucoperichondrial flap before septoplasty does not decrease the level of postoperative pain.
Keywords: preemptive anesthesia; septoplasty; pain score; VAS